On Decompositions of Intra-Regular and Left Regular Ordered ?-Semigroups: Chong-Yih Wu - Team, Support (Thai Journal of Mathematics, 2018)
Let S be an intra-regular or left (resp. right) regular ordered ?- semigroup with order preserving involution ?. Structure theorems referring to the decompositions of such semigroups into their simples subsemigroups are developed. Also in view of semilattice congruences we characterize intra-regular ordered ?- semigroups in which any two ideals are comparable under inclusion relation ⊆.